Influence of Strut Diameter and Building Direction on Strength of Lattice Structure - Hanzl, Pavel; Zetková, Ivana; Cajthamlová, Šárka (Manufacturing Technology Journal, 2019)
Metal additive manufacturing provides an efficient way of processing metallic cellular structures. This relatively novel way of production is based on a powder bed which is melted using a powerful laser. Despite the advantages of this production technology, differences in geometry are observed between the CAD model and the manufactured structures. With this in mind, a series of thin struts were made and their geometry analysed using optical-scanning microscopy. Various building directions and strut diameters are studied. The effective stiffness of struts are measured and verified by tensile tests. The results point to higher strength of inclined struts than perpendicular specimens.
Keywords: Milling Tool; Topological Optimization; Direct Melting Laser Sintering; Metal Additive Manufacturing